Terapi Menulis Ekspresif terhada Pengungkapan Diri (Self Disclosure) pada Orang dengan HIV/AIDS - Ni Wayan Lita Perdani; I Wayan Candra; I Gusti Ayu Harini; I Nengah Sumirta (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2021)
Expressive writing is an activity to express feelings and thoughts that have been experienced that describe the contents of the heart related to emotions in the form of writing that is described appropriately. Expressive writing therapy can be used as an effort to make oneself more open, one of which is in the case of HIV/AIDS. HIV/AIDS can cause many disturbances to sufferers, in addition to physical disorders, HIV/AIDS can also cause psychological disorders, not a few people with HIV/AIDS prefer to cover themselves. This study aims to determine the effect of expressive writing therapy on self-disclosure in people with HIV/AIDS. The design of this study was pre-experimental with the type of research being one group pre-test-post-test design. The sampling technique used is purposive sampling. The number of samples is 15 people. The research instrument used was The 32-item Revised Self Disclosure Scale. This study uses a non-parametric hypothesis test, namely the Wilcoxon Signed Rank Test. The results showed that the level of self-disclosure before being given treatment had a low level of self-disclosure as many as 5 people (33.3%), being 10 people (66.7%) and after being given treatment there was an increase in score with the results of the low category being 1 person (6 ,7%) and moderate to 14 people (93.3%). There was a significant effect in giving expressive writing therapy on the level of self-disclosure in people with HIV/AIDS with (p = 0.001). Expressive writing therapy can increase the level of self-disclosure in people with HIV/AIDS, that expressive writing therapy is effectively used to increase the level of self-disclosure of people with HIV/AIDS.